Supporting Teacher Candidates' Sense-Making of Field Instructors Feedback Through Co-constructed Goal-Setting - Elizabeth Soslau; Vicki Goettel; Deirdre Lilly (University of Windsor, 2018)
The purpose of this study was to discern if teacher candidates and their university-based field instructors engagement in co-constructed goal-setting activities would better support teacher candidates' understanding of feedback delivered during post-lesson observation conferences. Data from preliminary and retrospective surveys were compared within and across treatment and control groups. Findings showed that teacher candidates (n = 9) who participated in co-constructed goal-setting activities grew more comfortable discussing their teaching and took on a greater responsibility in guiding the post-observation conferencing discourse and higher rates than control-group participants (n = 9). However, the co-constructed goal-setting protocol did not support a greater understanding of feedback.